Performance of Different Catalysts on Biodiesel Production from Jatropha curcas Oil through Transesterification - Sujan, SM Asaduzzaman; Jamal, MS; Haque, M Naimul; Miah, M Yunus (Bangladesh Journal of Scientific and Industrial Research, 2010)
The purposes of the work to study the fatty acid methyl ester production by transesterification of Jatropha curcus oil with different catalysts where methanol was used as solvent. Jatropha oil having high free fatty acids FFA (14.02%) was processed in two steps. First step is acidcatalyzed esterification by using 1% H2SO4, 40% methanol-to-oil to produce methyl esters by lowering the acid value, and next step is different base-catalyzed transesterification. As part of ongoing efforts to investigate different homogeneous, heterogeneous and solid acid catalysts for biodiesel synthesis, the catalytic activity of KOH, NaOH, Ca(OH)2, activated Ca(OH)2, Hß zeolite and montmorillonite were studied for the transesterification of Jatropha oil. Among these catalysts, performance of catalysts order are KOH > NaOH > activated Ca(OH)2 >Ca(OH)2> montmorillonite> Hß zeolite. Key words: Jatropha oil; Transesterification; Biodiesel; FFA; Catalysts DOI: 10.3329/bjsir.v45i2.5702 Bangladesh J. Sci. Ind. Res. 45(2), 85-90, 2010